Talking across generations: Family communication about BRCA1 and BRCA2 genetic cancer risk. Issue 3 (29th January 2019) - Young, Alison Luk; Butow, Phyllis N.; Rhodes, Paul; Tucker, Katherine M.; Williams, Rachel; Healey, Emma; Wakefield, Claire E.
Abstract: While family communication about a BRCA1 or BRCA2 ( BRCA1/2 ) pathogenic variant can be a catalyst for the uptake of risk‐reducing measures in young adults, disseminating information within families and across generations is complex. This study aimed to explore how young adults and their families communicate about a BRCA1/2 pathogenic variant, from a family systems perspective. In‐depth family interviews and questionnaires ( N  = 67 individuals; 21 families) were completed at four metropolitan and regional genetic clinics in Australia. Data involved thematic analysis and interpretation based on family systems theory, including the use of standardized measures. Six key themes were identified and explored: (1) Responsibility to protect, (2) "It's a woman's problem, " (3) Family culture influences communication, (4) Adversarial growth and connection, (5) Key events can be relational turning points, and (6) Health professionals can help. Family identities were solidified through the incorporation of a pathogenic variant in family scripts, while members of the family who held differing views to their families expressed less agreeableness and openness to disseminate information. The collective family's experience and perspective toward a pathogenic variant can influence a young adult's decision‐making about genetic testing, risk‐management, and family planning. The utilization of family therapy skills in routine practice would be helpful in facilitating communication and the inclusion of standardized measures is beneficial to identify individuals needing ongoing psychological support. Understanding relationship difficulties that arise from family members holding divergent views can offer insight into future research inquiry and areas of further training and clinical support.